A CLINICAL CASE OF PULMONARY MYCOBACTERIOSIS IN THE PATIENT SUFFERING FROM DISSEMINATED TUBERCULOSIS - Zh. A. Lаushkinа; O. I. Аlkhovik (Туберкулез и болезни лёгких)
The article describes a clinical case of concurrent disseminated pulmonary tuberculosis and non-tuberculous mycobacterial pulmonary lesions caused by М. fortuitum in the HIV negative patient. This clinical case proves the need to isolate the culture of the causative agent and to type mycobacteria for accurate and timely diagnostics and prescription of effective etiotropic individual therapy.